The embodied mind extended: using words as social tools - Borghi, Anna M.; Scorolli, Claudia; Caligiore, Daniele; Baldassarre, Gianluca; Tummolini, Luca (Frontiers in Psychology, 2013)
The extended mind view and the embodied-grounded view of cognition and language are typically considered as rather independent perspectives. In this paper we propose a possible integration of the two views and support it proposing the idea of ''Words As social Tools' (WAT)'. In this respect, we will propose that words, also due to their social and public character, can be conceived as quasi-external devices that extend our cognition. Moreover, words function like tools in that they enlarge the bodily space of action thus modifying our sense of body. To support our proposal, we review the relevant literature on tool use and on words as tools and report recent evidence indicating that word use leads to an extension of space close to the body. In addition, we outline a model of the neural processes that may underpin bodily space extension via word use and may reflect possible effects on cognition of the use of words as external means. We also discuss how reconciling the two perspectives can help to overcome the limitations they encounter if considered independently.